Study of tuberculosis and other infections among children (age 2 to 18 years) with multitransfused thalassemia major - Gunjan V. Ramani; Makwana, Namrata K.; Bhadresh Vyas; Mahesh Jani (International Journal of Contemporary Pediatrics, 2023)
Background: In India, beta thalassemia is prevalent across the country, with an average frequency of carriers being 3-4%. Infection is the major cause of morbidity and mortality in thalassemia, so regular screening is required for this disease. Methods: Ethical clearance taken from institutional ethical committee. 150 thalassemia patients were enrolled in study after informed written consent. The medical histories were obtained from the patients and their files. Clinical examination was done including anthropometry, general examination, and systemic examination. MT and chest X-ray (CXR) were done for screening of tuberculosis infection. Blood samples were taken for S. ferritin, S. creatinine, serum glutamic pyruvic transaminase (SGPT), human immunodeficiency virus (HIV), and hepatitis B surface antigen (HBsAg) tests. Transfusion and other detail were taken like iron chelator, folic acid (FA) and calcium supplements. Results: In this study, out of 150 patients, 4 patients were RVD positive and 34 patients were HCV positive. No Patients found HBsAg positive. No patient had Montoux test reactive and chest X-ray positive finding. Conclusions: : Increase frequency of transfusion-related infection (hepatitis C, B, and HIV) in multi-transfused thalassemia. No correlation was found between tuberculosis infection and thalassemia patients in this screening study.